Implementasi Konseling Individu Melalui Teknik Punishment Dalam Mengurangi Perilaku Merokok Siswa Di Sma Negeri 1 Simpang Rimba Kabupaten Bangka Selatan - Wahyudi, Wahyudi; Santiya (Department of Islamic Guidance and Counseling, 2025)
This study aims to examine the implementation of individual counseling services using the punishment technique in reducing students’ smoking behavior and the impact following its application. The research background is based on the existence of smoking behavior among students that disrupts discipline and health and contradicts school regulations. Individual counseling services were chosen as an approach capable of addressing students’ problems personally, while the punishment technique was applied as an educational consequence to create a deterrent effect. This research employed a qualitative descriptive approach, with the subjects consisting of a guidance and counseling teacher and several students who had a smoking habit. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing. The study also applied B.F. Skinner’s Operant Conditioning theory and the Transtheoretical Model of Change to analyze behavioral changes among students. The findings revealed that the implementation of individual counseling with the punishment technique was carried out in sequential stages: initial, core, closing, and follow-up. The punishment applied was educational, including assignments, reprimands, and restriction of certain privileges while maintaining humanistic values. The impact of the counseling varied; some students showed decreased smoking frequency and increased self-awareness, while others remained resistant to change. Overall, individual counseling using the punishment technique was proven to contribute to reducing students’ smoking behavior, although its effectiveness was largely influenced by internal and environmental factors. Keywords:Individual Counseling, Punishment Technique, Smoking Behavior